Worsening dietary and physical activity behaviors do not readily explain why smokers gain weight after cessation: a cohort study in young adults - Tian, J; Gall, S; Smith, K; Dwyer, T; Venn, A (Oxford University Press, 2016)
The relationship between smoking cessation and weight gain is well established but the underlying mechanisms remain poorly understood. We aimed to determine whether postcessation weight gain was mediated by changing health behaviors.A total of 281 smokers self-reported their demographic, smoking, and lifestyle characteristics in 2004-2006 (aged 26-36) and 2009-2011 (aged 31-41). Behaviors considered as potential mediators of weight gain were changes in consumption of breakfast, discretionary foods (servings/d), fruit and vegetables (servings/d), alcohol (g/d), takeaway food (times/wk), Diet Guideline Index score, leisure time physical activity (PA, min/wk), total PA (min/wk), time spent sitting (min/d), and TV viewing (h/d).In total, 124 smokers quit smoking during 5 years follow-up. After adjustment for age, sex, baseline body mass index, education, and follow-up length, smoking cessation was associated with average excess weight gain of 2.09kg (95% CI = 0.35-3.83). Compared with continuing smokers, quitters reported a higher Diet Guideline Index score and less consumption of alcohol at baseline and follow-up (all p < .05). In addition, there was a tendency towards healthier dietary and PA behaviors over 5 years among quitters than continuing smokers except for time spent sitting, although these differences did not reach statistical significance. Adjustment for changes in these behaviors made little difference to the magnitude of postcessation weight gain (β: 2.32kg, 95% CI = 0.54-4.10).The weight gain associated with smoking cessation was not explained by worsening dietary and PA behaviors. Future research is needed to elucidate the complex mechanisms and particularly ways it may be prevented.Fear of weight gain often discourages smokers from trying to quit but guidance on ways to most effectively avoid weight gain is lacking. It is important to identify what causes postcessation weight gain and the ways it may be prevented. The current study explored the effects of several changing dietary and PA behaviors on the relationship between smoking cessation and weight gain in 281 young Australian smokers. We found that quitters tended to adopt healthier dietary and PA behaviors than continuing smokers, so these behaviors did not readily explain the postcessation weight gain. Further investigations of other potential mechanisms are needed.